Towards a Vectorial Approach to Predict Beef Farm Performance - Abbona, Francesca (2022)
Abbona, F., Vanneschi, L., & Giacobini, M. (2022). Towards a Vectorial Approach to Predict Beef Farm Performance. Applied Sciences, 12(3), 1-16. [1137]. https://doi.org/10.3390/app12031137 ------------------------------------ Funding: This work was partially supported by FCT, Portugal, through funding of projects BINDER (PTDC/CCI-INF/29168/2017) and AICE (DSAIPA/DS/0113/2019).